"I need someone who can convince me that life is worth living": Experiences from existential groups led by healthcare chaplains in Norwegian mental healthcare - Frøkedal, Hilde; Austad, Anne (Tidsskrift for Praktisk Teologi, 2019)
This article explores patients’ experiences of participating in existential groups led by Norwegian healthcare chaplains within mental health specialist services. A qualitative analysis based on the patients’ (N = 157) answers to two open-ended responses in a questionnaire was undertaken. This showed that most of the patients evaluated the groups positively, stating that participating in the existential groups allowed them to increase their self-reflection, let out their feelings, learn new skills, strengthen their self-confidence, and reduce their loneliness. Further, the groups were described as providing spiritual/religious growth and enhanced existential reflection. These results are discussed in relation to a pluralist context and the importance of existential meaning-making formental health.